2006
DOI: 10.1590/s1806-37132006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Variação sazonal nos atendimentos de emergência por asma em Gama, Distrito Federal

Abstract: Visits to the emergency room for the treatment of asthma attacks were more frequent during the rainy season, increasing at one to two months after the annual increase in humidity and decreasing in the dry season. This positive correlation raises the possibility of a causal relationship with proliferation of house dust mites and molds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
1
13
1
10
Order By: Relevance
“…Alguns estudos têm mostrado a relação entre a variação sazonal e as proporções de atendimentos ambulatoriais por doenças respiratórias (DR), assim como a ocorrência de internações hospitalares [1][2][3][4][5] .…”
Section: Introductionunclassified
“…Alguns estudos têm mostrado a relação entre a variação sazonal e as proporções de atendimentos ambulatoriais por doenças respiratórias (DR), assim como a ocorrência de internações hospitalares [1][2][3][4][5] .…”
Section: Introductionunclassified
“…Valença et al 14 , em um estudo realizado em Gama, no Distrito Federal, verificaram aumento de crises de asma 2 meses após o aumento do índice pluviométrico relacionado também ao tempo em que os fungos e ácaros levam para aumentar a sua concentração.…”
Section: Discussionunclassified
“…Rodrigues et al 34 verificaram que as maiores taxas de hospitalização por asma em idosos na Amazônia brasileira têm ocorrido no período de seca, contrapondo-se ao estudo de Valença et al 14 . Alguns fatores inerentes à população idosa podem explicar esse achado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…12 Some studies have demonstrated a seasonal relation in terms of hospitalizations and outpatient medical visits for asthma in several regions of Brazil. 13,14 With regard to the Brazilian Amazon, several studies have highlighted the importance of the association between climatic seasonality and occurrence of respiratory diseases, mainly in the drought season. 15,16 This region is characterized by well-established drought and rainy seasons.…”
Section: Introductionmentioning
confidence: 99%